Analysis of Scholarship Website Users Using the End-User Computing Satisfaction Model and Importance Performance Analysis Model - Ramadiani Ramadiani; Muhammad Reyhan Setiawan; Muhammad Labib Jundillah (Politeknik Pertanian Negeri Samarinda, 2026)
The East Kalimantan Scholarship Website is a facility provided by the government of the East Kalimantan Provincial Education and Culture Office. This study aims to assess the user satisfaction of individuals using a scholarship website by applying two well-established models: End-User Computing Satisfaction (EUCS) and Importance-Performance Analysis (IPA). The EUCS model evaluates users’ satisfaction with key aspects of the website. The IPA model is employed to assess the relative importance and performance of these factors from the user’s perspective, enabling the identification of areas for improvement. The combined insights from these models can guide the enhancement of scholarship website services and user experience. Data was collected through questionnaires to respondents, who registered on the BKT site with the Complete category from various universities. The East Kalimantan Scholarship website evaluation system calculates the results of questionnaires from students with various study programs. This system uses EUCS statements in the categories of Content, Accuracy, Format, Ease of Use, Timelines, and User Statistics. The results of this study indicate that the hypotheses designed are all accepted and have a significant influence. Users are satisfied with the website's ease-of-use aspect, which is the strongest aspect in supporting user satisfaction. Conversely, the accuracy aspect shows the weakest relationship among other variables.